2011
DOI: 10.1124/dmd.111.041558
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Metabolism and Disposition of SB939 (Pracinostat), an Orally Active Histone Deacetylase Inhibitor, and Prediction of Human Pharmacokinetics

Abstract: ABSTRACT:The preclinical absorption, distribution, metabolism, and excretion (ADME) properties of Pracinostat [(2E)-3-[2-butyl-1-[2-(diethylamino) ethyl]-1H-benzimidazol-5-yl]-N-hydroxyarylamide hydrochloride; SB939], an orally active histone deacetylase inhibitor, were characterized and its human pharmacokinetics (PK) was predicted using Simcyp and allometric scaling. SB939 showed high aqueous solubility with high Caco-2 permeability. Metabolic stability was relatively higher in dog and human liver microsomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…The human PK of Pracinostat was simulated with the Simcyp ADME simulator (Jamei et al, 2009) using the physico-chemical and in vitro ADME data. The simulated PK profiles were in good agreement with the observed mean data, and the mean oral clearance and AUCs were predicted reasonably well (within 2 fold of observed data) (Jayaraman et al, 2011). Furthermore, simulations of drug-drug interactions (DDI) of Pracinostat in humans with the potent CYP3A inhibitor and inducers, ketoconazole and rifampicin, respectively, and with omeprazole (substrate of 2C19) showed lack of potential DDI at the clinically relevant dose of 60 mg (Jayaraman et al, 2011).…”
Section: Pracinostat (Sb939)supporting
confidence: 62%
See 2 more Smart Citations
“…The human PK of Pracinostat was simulated with the Simcyp ADME simulator (Jamei et al, 2009) using the physico-chemical and in vitro ADME data. The simulated PK profiles were in good agreement with the observed mean data, and the mean oral clearance and AUCs were predicted reasonably well (within 2 fold of observed data) (Jayaraman et al, 2011). Furthermore, simulations of drug-drug interactions (DDI) of Pracinostat in humans with the potent CYP3A inhibitor and inducers, ketoconazole and rifampicin, respectively, and with omeprazole (substrate of 2C19) showed lack of potential DDI at the clinically relevant dose of 60 mg (Jayaraman et al, 2011).…”
Section: Pracinostat (Sb939)supporting
confidence: 62%
“…Pracinostat was found to selectively accumulate in tumors which correlated well with increased and prolonged acetylation levels in tumor which, in turn correlated with high tumor growth inhibition in mice (Novotny-Diermayr et al, 2011). Preclinical ADME of Pracinostat was characterized by: a) in in vitro liver microsomal stability studies, Pracinostat was most stable in human and dog, moderate in mouse, and least stable in rat; b) uniform PPB of 84-94% in preclinical species and humans; c) was metabolized mainly by human CYP3A4 and 1A2; d) did not inhibit the major human CYPs except moderate inhibition of 2C19 (~ 6 µM); e) lack of significant induction of human CYP3A4 and 1A2 in vitro; f) metabolite identification studies using liver microsomes showed the formation of N-deethylation and bis-N-deethylation as major metabolites in addition to minor oxidative products; g) a glucoronidation product of SB939 was found as the major metabolite in rat urine following oral dosing; h) PK: high systemic clearance of 9.2, 4.5 and 1.5 L/h/kg in mice, rat and dog, respectively and high volume of distribution (V ss ranged between 1.7 to 4.2 L/kg) in preclinical species; i) moderate F in mice and dogs and poor in rats (Jayaraman et al, 2011). In PK/PD studies in HCT116 xenograft models, studying the relationship between tumor growth inhibition and the PK/PD indices such as AUC/IC 50,HCT116 , C max / IC 50,HCT116 , and time above IC 50,HCT116 , Pracinostat was found to have the highest PK/PD ratios for all the three PK/PD parameters when compared to Vorinostat, Panabinostat and Belinostat (figure 1) (Jayaraman et al, 2009).…”
Section: Pracinostat (Sb939)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we tested the in vitro and in vivo antiplasmodial efficacies of a new, orally bioavailable, hydroxamate-based HDAC inhibitor undergoing clinical trials for cancer (35,47,52,65,67). SB939 (pracinostat; S*BIO), a pan-HDAC inhibitor acting on class I, II, and IV HDACs (47,65), has a longer in vivo half-life (t 1/2 of 2.4 h) than those of other hydroxamate-based HDAC inhibitors, such as SAHA (t 1/2 of 0.75 h) ( Table 1).…”
mentioning
confidence: 99%
“…It also provides a basis to develop in vitro to in vivo extrapolations (IVIVE) and to predict potential interactions between compounds, which gives a basis to take into account TK interactions for hazard characterisation of multiple compounds (chemical mixtures) (Coecke et al, 2006;Chen et al, 2011;Jayaraman et al, 2011;Kumar et al, 2011;Abass et al, 2013;EFSA, 2013). It also provides a basis to develop in vitro to in vivo extrapolations (IVIVE) and to predict potential interactions between compounds, which gives a basis to take into account TK interactions for hazard characterisation of multiple compounds (chemical mixtures) (Coecke et al, 2006;Chen et al, 2011;Jayaraman et al, 2011;Kumar et al, 2011;Abass et al, 2013;EFSA, 2013).…”
Section: Metabolismmentioning
confidence: 99%